Women Economic and Social Empowerment in Urban Middle Class Egyptian Households post 2016 Austerity Measures - El-Kady, Maha (AUC Knowledge Fountain, 2022)
Women empowerment has for long been part of all development agendas as part of the developing economies' social and economic reform plans. However, statistics do not usually reflect much improvement in the status of women’s empowerment, especially under austerity. And while most research focuses on the agony and vulnerability of poorer women, a big gap emerges with regard to middle classes women, who try hard to maintain the status of their households and not fall into poverty. This research attempts to cover part of this gap by investigating the social and economic empowerment of urban middle classes Egyptian women post-2016 IMF loan and related austerity measures. The research follows a qualitative approach of ten in-depth interviews with women from different spectrums within the middle classes. It concludes that while participants practiced and enjoyed much empowerment financially, they were not equally empowered socially. And this empowerment can be compromised in some instances due to the unchanged position of women within the governing social norms.